Marine debris monitoring and awareness program - Azman, Muhammad Afiq; Ramli, Muhammad Zahir (2019)
Kuantan is the capital state of Pahang. Being the one of the most prominent cities of the east coast peninsular, it host many beaches that lay before the world’s important water namely the South China Sea. Due to its strategic geographical location, the Kuantan coastlines are also renowned spots for tourism and fishing activities.